1) 2,3 * ( -8) - 9,8 :(6,7 - 8,1) = -18,4 - 49/5 : ( - 1,4) = - 18,4 - 49/5 : ( - 7/5) = -18,4 + 49/5 * 5/7 = -18,4 +7 = -11,4
2)(-28,6 : 57,2 - 26,8 :( -1,34)) * (-3,1) = (-0,5 - 134/5 : (-67/50)) * (-3,1) = (-0,5 + 134/5 * 50/67) * (-3,1) = (-0,5+2 * 10) * (-3,1) = (-0,5+20) * (-3,1)= 19,5*(-3,1) = -60,45
3)(-1,7 + 3,64 :(-1,4)):(-0,001)*(-0,40 = (-17/10+91/25:(-7/5)):(-1/1000)*(-2/5)=(-17/10-91/25*5/7):(-1/1000)*(-2/5) = (-17/10-13/5) : (-1/1000)*(-2/5) = -43/10:(-1/1000)*(-2/5) = -4,3:(-1/1000)*(-2/5) = -43/10 : (-1/1000)*(-2/5) = -43/10*1000*2/5 = -43*100*2/5 = -43*20*2=-1720